MODERASI BERAGAMA BERBASIS BUDAYA DAN KEARIFAN LOKAL PADA MASYARAKAT DONGGO DI BIMA (TINJAUAN SOSIO-HISTORIS) - Aksa Aksa; Nurhayati Nurhayati (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
This paper describes religious moderation based on culture and local wisdom in the Donggo community in Bima. This paper examines the standpoint of culture and local wisdom in assessing religious moderation for the Donggo community. This research is a historical research with a socio-cultural approach. The input methodology is the flow of the flow in the historical methodology which takes the stages of heuristic, criticism, interpretation and historiography. The results showed that the Donggo area (Dana Donggo) is a place for culture and local wisdom as well as a role model for diversity in the midst of religious plurality. Interestingly, religious moderation in the Donggo (Dou Donggo) community is actually united by a variety of cultural expressions and local wisdom, not because of religious factors. Meanwhile, religious moderation is increasingly taking root in the midst of religious plurality because it is supported by the use of symbols, identities and rites of ‘Raju Culture’ as social glue without religious barriers.